1998
DOI: 10.1302/0301-620x.80b4.0800731
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-dried and gamma-irradiated tendon allografts in rats

Abstract: We examined solvent-dried, gamma-irradiated (SD-R) allografts and fresh-frozen (FF) allografts mechanically and morphologically. Before transplantation, FF grafts were more than six times stronger than SD-R grafts. After four weeks, the tensile strength was about the same in both groups. At 24 weeks only collagen fibrils of small diameter were observed in the SD-R grafts while in FF grafts fibrils of small and intermediate diameter were seen. Clinically, we suggest that SD-R grafts could be used as a favourabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Therefore, preservation and sterilization of tendon allografts are required to prevent these problems, although this tissue processing has a potentially negative effect on the quality of the graft. Several authors have reported the effects of processing of tendon allografts on reconstruction (Maeda et al 1997(Maeda et al , 1998Noyes and Grood 1976;Woo et al 1986). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preservation and sterilization of tendon allografts are required to prevent these problems, although this tissue processing has a potentially negative effect on the quality of the graft. Several authors have reported the effects of processing of tendon allografts on reconstruction (Maeda et al 1997(Maeda et al , 1998Noyes and Grood 1976;Woo et al 1986). …”
Section: Introductionmentioning
confidence: 99%